2017
DOI: 10.1093/brain/awx179
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of fast-spiking cells in ictal sequences during spontaneous seizures in rats with chronic temporal lobe epilepsy

Abstract: See Lenck-Santini (doi:) for a scientific commentary on this article. Using population recordings in two rat models of chronic temporal lobe epilepsy, Neumann, Raedt et al. show that ictal spikes are accompanied by characteristic sequential patterns of neuronal activity. The neurons that are strongly activated during ictal events are predominantly fast-spiking interneurons, and not excitatory principal cells as previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 100 publications
(117 reference statements)
10
37
0
Order By: Relevance
“…Around 30% of neurons significantly increased or decreased their firing at the seizure onset. In line with recent observations showing that the inhibitory neurons provide the largest contribution to the LFP in their close neighbourhood 22 and are predominantly activated during ictal events, 23 firing of only a relatively limited number of interneurons at the microscopic scale might be sufficient to produce high-frequency components at the EEG level. We found no correlation between periods with disappearance of single units and periods with decreased signal quality in the local field potential (LFP) band or increased multiunit activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Around 30% of neurons significantly increased or decreased their firing at the seizure onset. In line with recent observations showing that the inhibitory neurons provide the largest contribution to the LFP in their close neighbourhood 22 and are predominantly activated during ictal events, 23 firing of only a relatively limited number of interneurons at the microscopic scale might be sufficient to produce high-frequency components at the EEG level. We found no correlation between periods with disappearance of single units and periods with decreased signal quality in the local field potential (LFP) band or increased multiunit activity.…”
Section: Discussionsupporting
confidence: 91%
“…9,11 Indeed, as shown in previous human studies, 11,21 EEG synchronization (reflecting nonlocal subthreshold inputs) can sometimes be dissociated from local cellular firings. In line with recent observations showing that the inhibitory neurons provide the largest contribution to the LFP in their close neighbourhood 22 and are predominantly activated during ictal events, 23 firing of only a relatively limited number of interneurons at the microscopic scale might be sufficient to produce high-frequency components at the EEG level. However, further studies using cell-type classifications are necessary to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…39 Single-unit recordings revealed that the powerful ictogenic effect of interictal interneuron activation probably resulted from rebound firing enhancement of pyramidal neurons following the optogenetic interneuron stimulation. 44 In patients with mesial-temporal lobe epilepsy during the onset of LVF seizures in hippocampus, inhibitory neurons dramatically increased their firing rate prior to an increase in excitatory neuron firing. 44 In patients with mesial-temporal lobe epilepsy during the onset of LVF seizures in hippocampus, inhibitory neurons dramatically increased their firing rate prior to an increase in excitatory neuron firing.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic epileptic animals, interneurons were preferentially recruited during spontaneous interictal activity in the CA1 region, 43 as well as before and during ictal events. 44 In patients with mesial-temporal lobe epilepsy during the onset of LVF seizures in hippocampus, inhibitory neurons dramatically increased their firing rate prior to an increase in excitatory neuron firing. 45 The general conclusion made from these data implies the dominating role of interneuron firing in the onset of both interictal and ictal events, with the delayed pyramidal cell firing as the result of postinhibition rebound excitation.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy, characterized by recurrent seizures, affects 65-70 million people worldwide (Moshé et al, 2015;Thijs et al, 2019). Although the hyperexcitability underlying epilepsy is believed to be caused by an imbalance of synaptic excitation and inhibition (Li et al, 2011;Neumann et al, 2017;Paz and Huguenard, 2015), antiepileptic strategies directly targeting neuronal excitability have proven to be insufficient in a significant proportion of patients (Löscher and Schmidt, 2006;Eyo et al, 2017;Ferlazzo et al, 2017). This insufficiency points to the need to identify the cause of the imbalance between excitation and inhibition.…”
Section: Introductionmentioning
confidence: 99%